2020
DOI: 10.3390/plants9060800
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Herbs, Medicinal Plant-Derived Essential Oils, and Phytochemical Extracts as Potential Therapies for Coronaviruses: Future Perspectives

Abstract: After its recent discovery in patients with serious pneumonia in Wuhan (China), the 2019 novel coronavirus (2019-nCoV), named also Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), has spread quickly. Unfortunately, no drug or vaccine for treating human this coronavirus infection is available yet. Numerous options for controlling or preventing emerging 2019-nCoV infections may be predicted, including vaccines, interferon therapies, and small-molecule drugs. However, new interventions are likely to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
82
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 94 publications
0
82
0
2
Order By: Relevance
“…Large scale drug and phytomedicine repurposing is being currently investigated as it is plausible that anti-retroviral therapy may also be effective against SARS coronavirus [ [57] , [58] , [59] , [60] ]. ‘BhAVI-23’ displayed prominent inhibition of HIV-1 RT activity as well as infectivity of P1 (vir) phage thus ascertaining its anti-viral potential.…”
Section: Discussionmentioning
confidence: 99%
“…Large scale drug and phytomedicine repurposing is being currently investigated as it is plausible that anti-retroviral therapy may also be effective against SARS coronavirus [ [57] , [58] , [59] , [60] ]. ‘BhAVI-23’ displayed prominent inhibition of HIV-1 RT activity as well as infectivity of P1 (vir) phage thus ascertaining its anti-viral potential.…”
Section: Discussionmentioning
confidence: 99%
“…In this view, various coumarin-based hybrids possessing diverse medicinal attributes have been synthesised in the past five years by conjugating a coumarin moiety with other therapeutic pharmacophores (37). Antiviral mechanistic studies of TCM, AM, and/or EHD have revealed how they interfere with the viral life cycle, as well as virus-specific host targets (4). Herbal drugs have demonstrated a wide range of antiviral mechanisms that include inhibition of 3CLpro protein (Chinese Rhubarb extracts, Houttuynia chordata extract, hesperetin, etc.…”
Section: Discussionmentioning
confidence: 99%
“…There is continuous interest in searching for alternative antiviral drugs between phytochemical extracts, medicinal plants, and aromatic herbs. Discovery and production of novel antiviral drugs comes frequently from spices, herbal medicines, essential oils (EOs), and distilled natural products (4). Coumarins comprise a large class of compounds found within medicine herbal preparations (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant advantage of using herbs in viral respiratory infections is due to their potent anti-inflammatory and immunostimulatory action (Patwardhan et al, 2020). Some of the active phytoconstituents in medicinal plants have inhibitory action on coronaviruses (Boukhatem and Setzer, 2020;Mani et al, 2020), however determination of functional actions on ACE2 is critical to elucidate agonist/activation or inhibitor/antagonist. Considering the pathogenesis of COVID-19, we identified some Indian medicinal plants with potent antiinflammatory, immunomodulatory, and antiviral activities for de- veloping potential treatment of COVID-19.…”
Section: Molecular Docking Against Ace2mentioning
confidence: 99%